PEMIKIRAN EKONOMI SOSIALIS TAN MALAKA DALAM PERSPEKTIF EKONOMI ISLAM - ZUWARDI, ZUWARDI (IAIN Batusangkar, 2017)
The purpose of this research is to ?ind out and explain the Socialist Economics, Tan Malaka, according to Islamic economics. This type of research was library research by using content analysis. The results showed that in the perspective of Islamic economics, the Socialist Economics, Tan Malaka has similarities in terms of objectives and goals. The form of the equation among others is the equality ofconcepts of justice, prosperity and welfare which are the goal of the economic system. This equation was also seen in the form of abolition of slavery and oppression.Beside the spirit of brotherhood, and mutual help or assistance proposed by Tan Malakawere also owned by Islamic economics. The role of the State in socialist economic policy Tan Malaka is also owned by Islamic economics. The prominent difference in Tan Malaka's socialist economy in terms of Islamic economics lies in the ways or instruments he uses such as zakat, infak, shadaqoh, waqf, banning ribs and so forth. In addition, differences are also seen in the philosophical foundations and rules that support the economic system.